SENEN ART HUB: MENGEMBALIKAN CITRA PUSAT HIBURAN DI KAWASAN SENEN - Vanesa Marcella; Rudy Trisno (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
According to Senen’s history, in 1930 Senen is known as a shopping and entertainment center. Back then, there are a group of teenager and artists who like to gather around in Senen and it became the pioneer of the largest art ecosystem in Jakarta. However, now Senen's condition has decreased in the mental (historical) aspect. The image of the entertainment center and arts ecosystem are vanished, as well as the unorganized condition of the area. The purpose of this research is to create  a space for artists' and community center. Senen has a big potential to bring back the memory as an entertainment center. In order to create an art and cultural tourism destination in Senen, art exhibitions and performances are the main attraction in this project. The used methods are a) Identification of problems in the related area; b) Area investigation; c) Site analysis; d) Use of design concepts; e) Zoning and program; f) The concept of mass composition and its formation; g) The final result such as exterior & interior design.The findings of this research are design indicators as an idea to restore the image of the entertainment center in Senen by applying urban acupuncture theory, logic of space, contextual concepts and Betawi culture in building. Keywords: Art; Artist; Degradation; History; Image; Senen Abstrak Dalam sejarah, kawasan Senen pada tahun 1930 menjadi pusat perbelanjaan serta pusat hiburan. Dilatar belakangi oleh kumpulan anak muda dan seniman yang gemar berkumpul di sekitar Senen menjadi cikal bakal ekosistem seni terbesar di Jakarta. Namun, sekarang kondisi Senen mengalami degradasi dalam aspek mental(history). Citra pusat hiburan dan ekosistem seni yang hilang, serta potensi kawasan Senen yang kurang dimanfaatkan. Tujuan penelitian ini adalah menciptakan ruang ekspresi seniman dan wadah masyarakat khususnya remaja untuk mengenalkan potensi kawasan Senen sebagai pusat hiburan dalam menikmati pameran dan pertunjukkan seni terbuka agar mengembalikan citra pusat hiburan di kawasan Senen. Metode perancangan dengan urban acupuncture, logic of space, konsep kontekstual dan kebudayaan Betawi menghasilkan tahapan a)Identifikasi masalah pada kawasan terkait; b) Investigasi kawasan; c)Analisis tapak; d) Penggunaan konsep perancangan; e) Zoning dan program ruang; f) Konsep gubahan massa dan pembentukannya; g) Hasil akhir berupa desain eskterior & interior. Temuan penelitian yang didapatkan sebagai hasil dari perancangan ini sebagai upaya pengembalian citra pusat hiburan di Senen dengan penerapan teori urban acupuncture, logic of space, konsep kontekstual dan kebudayaan Betawi.